Impact of empowerment on public participation awareness in community renewal projects: mediating role of trust and community identity - Chunling Sun; Jingjing Liu; Yifei Chen (Journal of Asian Architecture and Building Engineering)
As urbanization progresses in China, community renewal becomes a crucial way to achieve sustainable urban development. However, as the focus of community regeneration, the public’s passive participation and lack of awareness of participation are the biggest obstacles to the community regeneration process. Empowerment (EP) stimulates the internal drive of the public in the community by empowering the subject with power, capacity, and energy. In view of this, the objective of this study is to reveal effective ways to enhance public participation awareness (PPA) in community renewal through empowerment. Through empirical analysis of the collected 300 valid questionnaires, the results show that: empowerment, community identity (CI), and trust relationship (TR) have a positive impact on PPA in community renewal, while CI and TR play a mediating role in the process. The results of the study provide new ideas to enhance public participation awareness in community renewal projects and provide certain decision-making advice to promote urban co-construction and sharing.